ANALISIS PERILAKU PENCEGAHAN DEMAM BERDARAH DENGUE: STUDI LITERATURE - dony setiawan hendyca putra; Hela Denia Pratiwi; Hendro Prasetyo; Akhmad Efrizal Amrullah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
Dengue Hemorrhagic Fever (DHF) is one of the main public health problems in Indonesia. The number of sufferers and the area of Dengue Hemorrhagic Fever (DHF) spread is increasing along with the increasing mobility, environment, climate, population density and community behavior, especially in tropical and sub-tropical areas. Methods: The search strategy used by researchers in making this Literature Review was to use the keyword "Dengue Hemorrhagic Fever Prevention Behavior". searches using databases are conducted, among others, at Google Scholar or Google Scholar. With a time span of 2010-2020. Results : Based on the results of the journal review, the prevention behavior of dengue fever by the family is influenced by the knowledge that the better the family's knowledge of Clean and Healthy Living Behaviors at home, the better the behavior of preventing dengue hemorrhagic fever in the family environment. Conclusion: the better the family's knowledge about PHBS in the household, the better the behavior to prevent Dengue Hemorrhagic Fever (DHF) in the family environment. And prevention through Clean and Healthy Behavior (PHBS) and 3M Plus, if done properly, will reduce the presence of mosquito larvae around the home environment.